Handwriting Analysis for Disease Identification - Asra, Syeda; Shubhangi, DC (International Journal of Computer Sciences and Engineering, 2018)
Handwriting is a tool to understand partially the unknown world of subconscious mind. The motor nerves come into play while writing. Personality trait identification can be done successfully with accuracy through handwriting. A research is done to show new avenues of application of handwriting analysis. Diseases like strokes, Alzheimer’s disease, Parkinson, Dyslexic disorders can be very easily diagnosed well in advance before the onset of the disease. A novel work is carried out to enlighten that, hand writing analysis not only identifies a person’s characteristic traits but also identifies many diseases including brain disorders like Alzheimer’s disease, suicidal tendency and pessimism etc.